Risk Factors and Impact of non-Aspergillus mold infections (NAMI) following Allogeneic HCT: A CIBMTR Infection & Immune Reconstitution analysis - Riches, Marcie L. (Bone Marrow Transplant, 2015)
Risk factors for non-Aspergillus mold infection (NAMI) and the impact on transplant outcome are poorly assessed in the current era of antifungal agents. Outcomes of 124 patients receiving allogeneic HCT diagnosed with either mucormycosis [n=72] or fusariosis [n=52] between days 0-365 after HCT are described and compared to a control cohort (n=11856). Patients with NAMI had more advanced disease [mucormycois 25%, fusariosis 23%, controls 18%; p = 0.004] and were more likely to have a KPS<90% at HCT [mucormycosis 42%, fusariosis 38%, controls 28%; p=0.048]. The 1-year survival after HCT was 22% (15–29%) for cases and was significantly inferior compared to controls [65%(64–65%); p < 0.001]. Survival from infection was similarly dismal regardless of mucormycosis [15% (8-25%)] and fusariosis [21% (11-33%)]. In multivariable analysis, NAMI was associated with a 6-fold higher risk of death (p<0.0001) regardless of the site or timing of infection. Risk factors for mucormycosis include preceding acute GVHD, prior aspergillus infection, and older age. For fusariosis, increased risks including receipt of cord blood, prior CMV infection, and transplant prior to May 2002. In conclusion, NAMI occurs infrequently, is associated with high mortality, and appears with similar frequency in the current antifungal era.